The difference in the effect of immersing heat-polymerized acrylic resin denture base in basil (Ocimum basilicum) leaf extract and chlorhexidine on the quantity of Candida albicans: study experimental - Nasution, Assajdah; Wahyuni, Siti; Tarigan, Slamat (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2025)
ABSTRACTIntroduction: Denture material that is often used as a base is heat-cured polymethyl methacrylate (PMMA) acrylic resin (hot polymerized acrylic resin). This material has microporosity which causes easy accumulation of food residue. Essential oils in basil leaves can inhibit several bacteria and fungi such as Candida albicans. This study aims to analyze the difference in the effect of immersing heat-polymerized acrylic resin (HPAR) denture base in basil (Ocimum basilicum) leaf extract at concentrations of 15%, 20%, 25%, as well as chlorhexidine, on the quantity of Candida albicans. Methods: This type of research is a laboratory study with RAPP denture base samples soaked in basil leaf extract 15%, 20%, 25%, and chlorhexidine for 15 minutes with samples measuring 10x10x1 mm as many as 30 samples. Each sample was measured using a spectrophotometer. Samples were analyzed by hapiro-Wilk, Kruskal-Wallis, and Mann-Whitney tests. Results: The results of the Kruskal-Wallis test showed that there was an effect of soaking RAPP denture base in basil leaf extract of 15%, 20%, 25%, and chlorhexidine after being compared with aquabidest (control) on the number of Candida albicans with a value of p = 0.019 (p <0.05). Conclusion: Immersing HPAR denture base in basil (Ocimum basilicum) leaf extract for 15 minutes has a significantly greater effect in inhibiting the growth of Candida albicans compared to chlorhexidine.KEY WORDS: Acrylic denture, chlorhexidine, basil leaf extract, acrilyc, Candida albicansPerbedaan pengaruh perendaman basis gigi tiruan resin akrilik polimerisasi panas dalam ekstrak daun kemangi (Ocimum basilicum) dan klorheksidin terhadap jumlah Candida albicans: Studi eksperimentalABSTRAKPendahuluan: Bahan gigi tiruan yang sering digunakan sebagai basis adalah resin akrilik polimethyl methacrylate (PMMA) jenis heat cured (resin akrilik polimerisasi panas). Bahan tersebut memiliki mikroporositas yang menyebabkan mudah terjadi akumulasi sisa makanan. Minyak atsiri pada daun kemangi mampu menghambat beberapa bakteri dan jamur seperti Candida albicans. Tujuan penelitian ini untuk menganalisis perbedaan pengaruh perendaman basis gigi tiruan resin akrilik polimerisasi panas dalam ekstrak daun kemangi (Ocimum basilicum) 15%, 20%, 25% dan klorheksidin terhadap jumlah Candida albicans. Metode: Jenis penelitian ini adalah penelitian laboratorium dengan sampel basis gigi tiruan RAPP yang direndam dalam ekstrak daun kemangi 15%, 20%, 25%, dan klorheksidin selama 15 menit dengan sampel berukuran 10x10x1 mm sebanyak 30 sampel. Setiap sampel diukur menggunakan spektrofotometer. Sampel dianalisis dengan uji Shapiro-Wilk, Kruskal-Wallis, dan Mann-Whitney. Hasil: Hasil uji Kruskal-Wallis menunjukkan bahwa, ada pengaruh perendaman basis gigi tiruan RAPP dalam ekstrak daun kemangi 15%, 20%, 25%, dan klorheksidin setelah dibandingkan dengan akuabides (kontrol) terhadap jumlah Candida albicans dengan nilai p=0,019 (p<0,05). Simpulan: Perendaman basis gigi tiruan RAPP dalam ekstrak daun kemangi selama 15 menit memiliki perbedaan pengaruh yang lebih signifikan dibandingkan dengan klorheksidin dalam menghambat pertumbuhan jumlah Candida albicans.KATA KUNCI: Gigi tiruan akrilik, klorheksidin, ekstrak daun kemangi, akrilik, candida albicans